Technologies and practices to improve feed and nutrient utilization by pigs - Navales, Ron Aldwin Sapin (My University, 2025)
In chapter 1, a literature review was conducted to summarize the current practices that producers can use to improve feed and nutrient utilization with a focus on providing critical information for use within future life cycle assessment of the swine industry. These practices include improvement of feed efficiency and nutrient utilization by pigs through diet nutrient levels, feed formulation, feed processing, feeding management, and non-nutritional factors such as genetics, environment, and health status. Research needs were also identified, with some investigated in chapters 2 to 4. Specifically, a total of two, one, and four trials were conducted to compare diet blending with phase feeding on growth performance and profitability of finishing pigs (Chapter 2), to determine the available P and total tract digestible P release curves for a novel phytase (Microtech phytase, Chapter 3), and to determine the effect of standardized ileal digestible (SID) Lys to crude protein (CP) ratio on growth performance and blood urea N of 45 to 125 kg pigs (Chapter 4). In Chapter 2, a total of 2,160 and 962 pigs were utilized in 2 experiments. Two feeding strategies (phase feeding and diet blending) were compared and concluded that both supported similar growth and carcass traits. Income over feed cost was generally unaffected, but diet blending reduced feed usage and feed cost per kg gain. In Chapter 3, a total of 320 barrows were used. Overall, the use of Microtech phytase improved growth performance. Additionally, the available P (aP) release curve based on the average percent bone ash of right fibula, 10th rib, and 3rd metacarpal and true total tract digestible (TTTD) P release curve developed for Microtech phytase are: aP release, % = (0.868 × FTU/kg) ÷ (9,599.511 + FTU/kg) and TTTD P release, % = (0.00004017 × FTU) + 0.011, respectively. In Chapter 4, a total of 2,517 pigs were used across 4 experiments. Overall, increasing SID Lys:CP ratio worsened gain to feed ratio and decreased blood urea N in 45 to 125 kg pigs. Based on the local maxima determined using cubic models, the estimated SID Lys:CP ratios to optimize gain to feed ratio were 5.55% (45 to 70 kg), 5.47% (55 to 78 kg), and 5.27% (103 to 125 kg). For 84 to 108 kg pigs, requirements were estimated below 5.13% (linear model). Overall, chapters 2 to 4 underscore the opportunities to improve feed and nutrient utilization through feeding strategy, diet formulation (i.e., use of phytase), and nutrient levels. Diet blending allows for reduction in feed usage while maintaining growth, phytase allows for reduction in the use of inorganic P and determining the optimum SID Lys:CP ratio allows for formulating low CP diets. This dissertation also evaluated the effect of dietary S-abscisic acid (S-ABA) supplementation on the growth performance and antioxidant status of nursery pigs (Chapter 5). A total of 320 nursery pigs were used and supplemented with increasing level of S-ABA. Overall, S-ABA supplementation did not influence growth performance, but improved the antioxidant status by reducing the erythrocyte oxidized to reduced glutathione ratio. In addition to the dissertation chapters, a retrospective study was added as an appendix, assessing the impact of sow body weight (BW) change during gestation on sow body weight change and litter average daily gain (ADG) during lactation. The dynamics of sow BW change during gestation and lactation significantly influenced litter ADG. Increased BW gain in gilts during gestation led to greater BW loss in lactation without negatively affecting litter ADG, whereas BW loss in sows during gestation led to compensatory gain during lactation at the expense of litter ADG.
Keywords: Life cycle assessment; Feeding strategy; Phytase; Nitrogen; Antioxidant; Litter gain